Infrared high-resolution spectra of ozone in the range 5500-5570 cm-1: analysis of v2+5v3 and v1+v2+4v3 bands - Barbe A.; Chichery A.; Tyuterev Vl. G.; Taskhun S. A.; Mikhailenko S. N. Semen Nikolaevich (1998, 1998)
Title screen